(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The geomorphology, Late Quaternary stratigraphy, sedimentology and hydrology of the upper basin of the Salado River were investigated. The study area is located in S Santa Fe and NW Buenos Aires provinces (11.000 km²) and comprises the NE sector of the Pampean Sand Sea (defined by Iriondo and Kröhling, 1995; Figures 1 and 2). The methodology applied in this study produced conclusions of stratigraphic and paleoclimatic nature. Works were performed in photographic and images cabinet, in the field and laboratory. In cabinet, the geological cartography produced by the first author in former projects was issued, particularly the geological map of Santa Fe province, in 1:500.000 scale (Iriondo, 1987; Figure 3), the map of the South American plains (Iriondo, 1990a; Petit Maire et al., 1999) and the map of the Pampean Sand Sea in scale 1:1.000.000 (Iriondo, 1992). That was complemented with satellite images and photomosaic analyses, integrated with classical topographic quadrangles of IGM. Field works made in the region covered a period of two decades. The first expedition was done in the year 1985, during a dry inter-annual period which favored the description of geological profiles and collection of fossils in the bottom of channels. Further expeditions were made in the 1990’s, resulting in the elaboration of the regional stratigraphy (Figure 4; Kröhling, 1998; Iriondo and Kröhling, 1995). The last three field surveys, between the years 2001 and 2004 (during the present humid period), were focused on the studies of dune fields, with areal sampling (about 50 samples) and the recovering of sedimentary cores (41 m drilled). Four stratigraphic boreholes were made in the study area and a complementary one outside it, with recovering of undisturbed samples and complemented with geotechnical S.P.T. tests. The main boreholes were drilled in Teodelina (34°11´lat. S; 61°31´long.W; 88 m a.s.l.; Santa Fe; Figure 5) and in San Gregorio (34°17’ lat. S y 61°55´ long. W; 102 m a.s.l, Santa Fe). Laboratory analises comprises grain size analysis by sieving at intervals of ¼ ? between 125 and 37 ?m. For mineralogical determinations were applied loose grain techniques (in the very fine sand fraction) and X-ray diffractometry (on total samples; Figure 6). Complementary, morphoscopic determinations were carried out in the 74 ?m fraction. Two geological formations of eolian origins are widespread in the region, Teodelina Fm (Late Pleistocene) and San Gregorio Fm (Late Holocene), which are formally defined here. The Teodelina Fm has a typical thickness of 10 to 12 m and has been eroded up to 5 m in some areas; it is composed of sandy coarse silt and silty fine sand, with main modes at 125-250 ?m and 53-62 ?m; the colour is yellowish brown and similar ones. The mineral composition of the 53-62 ?m fraction is dominated by volcanic glass, with feldspars, quartz and alterites as accessory minerals. Roundness and sphericity of the grains vary from low to moderate, with two populations. The San Gregorio Fm is more than 7 m thick. It is composed of loose, massive, yellowish brown in color, very fine to fine sand (Figures 7a and 7b). The mineral composition is dominated by vitreous shards, alterites and feldspars as its main components and quartz as a secondary component; main heavy minerals were originated in the Pampean Ranges. The geomorphology of the area and the present hydric dynamics are controlled by eolian geoforms generated during the Late Quaternary. The exception is the fluvial collector in S Santa Fe which is a paleochannel of the Tercero river, controlled by tectonics (Figure 8). The study area underwent a sequence of dry and humid episodes during the Late Quaternary. Basically, the present landscape is the result of the influence of a humid climate which took place in the Oxygen Isotopic Stage 3 (OIS 3; 64-36 ka) and the eolian activity produced by a dry climate in the Late Holocene (3.5- 1.4 ka). The sequence of sedimentary and geomorphic events deduced from the data of this research was the following: during the humid OIS 3, a fluvial net developed; it forms at present the upper basin of the Salado River of Buenos Aires, and is carved in the Carcarañá Formation (OIS 3; Kröhling, 1999). In a subsequent dry episode (Late Pleistocene), the Teodelina Formation was sedimented by eolian and associated processes. A largelly erosive eolian phase occurred after Teodelina Fm accumulation; it was characterized by Western winds that carved hundreds of large deflation hollows. A discontinuous sedimentation of a sandy loess up to 2 m thick with bimodal grain size distribution covered the minor accidents of the landscape. The humid period of the Middle Holocene (8.5-3.5 ka) was characterized by a warm and humid climate with an udic soil regime, which generated a soil profile on the loessic terrains and provoked the water level rising in lakes and swamps. The Late Holocene, from 3.5 to 1.4 ka BP, was characterized by a dry climate that produced the development of parabolic dune fields, named here as the San Gregorio Formation. An interesting geomorphological feature of the study area is represented by numerous shallow lakes occupying large deflation hollows generated by W winds. That indicates a shift of the Westerlies to the N up to 34° lat. S at the Upper Pleistocene-Lower Holocene interval (Figure 9). During the Little Ice Age the studied area underwent an arid climate with dominance of SW winds that produced a general mobilization of sand to the NE (Figure 10); the inherited shallow lakes were transformed in playas (Dangavs and Mormeneo, 2006). The present dynamics is dominated by an excess of water in the landscape as a consequence of the Present humid climate and the morphosedimentological control referred above. The significant sedimentological process is the mobilization of large volumes of dissolved salts, mainly chlorides and sulphates.